Among Indian rajahs and ryots : a civil servant's recollections & impressions of thirty-seven years of work & sport in the Central Provinces & Bengal - Fraser, Andrew H. L. (Andrew Henderson Leith), Sir, 1848-1919 (Chugh Publications, 1975)
Reminiscences, 1871-1908.